2015
DOI: 10.1149/2.1001507jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Bright Al Coatings from 1-Butyl-3-Methylimidazolium Chloroaluminate Ionic Liquids with Specific Additives

Abstract: The electrodeposition of aluminum (Al) on copper (Cu) substrate was investigated in [Bmim]Cl/AlCl 3 (33.3/66.7 mol%) ionic liquid using three pyridine derivatives, nicotinic acid, methyl nicotinate, and 3-methyl pyridine as additives at 303 K, respectively. It was found that bright Al coatings could be electrodeposited with nicotinic acid and methyl nicotinate as additives. SEM and XRD characterizations revealed that the bright coatings were very smooth, composed of nanocrystalline and with a strong (200) pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…The presence of the co‐solvent promotes lower viscosity and higher conductivity in the electrolyte, in comparison with bare melts, facilitating the plating process. Regarding the use of organic additives as brighteners, nicotinic acid and methyl nicotinate (2.0 to 8.0 mmol) have given good results on small flat surfaces (10 mm×10 mm) whereas 1,10‐phenantroline (27.7 mmol) was tested on car wheel bolts.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the co‐solvent promotes lower viscosity and higher conductivity in the electrolyte, in comparison with bare melts, facilitating the plating process. Regarding the use of organic additives as brighteners, nicotinic acid and methyl nicotinate (2.0 to 8.0 mmol) have given good results on small flat surfaces (10 mm×10 mm) whereas 1,10‐phenantroline (27.7 mmol) was tested on car wheel bolts.…”
Section: Introductionmentioning
confidence: 99%
“…Some additives can increase the polarization of the cathode. [57,58,74,75] The adsorption of additives on the electrode surface can change the cathode potential, thus resulting in an increase in current density and the corresponding increase in current efficiency. However, there are some additives that can decrease cathodic polarization, such as pyridine derivatives.…”
Section: Sem Characterizations Of the Metal Coatingmentioning
confidence: 99%
“…Recently, we found nicotinamide and methyl nicotinate were effective leveling agents and brighteners for Al deposition based on the results of cyclic voltammetry and AFM. Through comparison, it was concluded that pyridine derivatives with electron‐withdrawing groups have stronger adsorption ability, enabling them to tailor Al deposition and producing better Al deposits . Moreover, the function mechanism of these additives was proposed as shown in Figure .…”
Section: Direct Electrodeposition From Ilsmentioning
confidence: 99%